DINAMIKA IBADAH KURBAN DALAM PERKEMBANGAN HUKUM ISLAM MODERN - B. Hariyanto (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2018)
Sacrifice is a necessity in the activities of Muslims every year. In addition to having a vertical dimension in the form of obedience to the commands of Allah SWT, sacrificial worship also has a horizontal dimension that is urgent for ukhuwah Islamiyah, namely concern for others and justice in realizing Muslim unity. The progress of the times achieved by modern civilization can actually be solutions that facilitate all forms of Islamic worship practices. Collective goat sacrifices, online sacrificial worship, sacrificial slaughter with mechanical devices, and sacrificial canning are some of the dynamics that occur in Muslim communities in the world. These dynamics must be addressed wisely in accordance with the objectives of the Shari'a. The progress of the era with all its derivatives requires every Muslim to continue to strive to understand and explore the philosophical and axiological meanings of all the worship carried out, including in the implementation of sacrificial worship.